The diffusion behavior and capacitance of tetraethylammonium/tetrafluoroborate ions in acetonitrile with different molar concentrations: a molecular dynamics study. Issue 87 (4th December 2017) - Yang, Po-Yu; Ju, Shin-Pon; Hsieh, Hua-Sheng; Lin, Jenn-Sen
Abstract : A molecular dynamics (MD) simulation with the optimized potentials for liquid simulations-all atom (OPLS-AA) force field was carried out to investigate the dynamic behaviors of organic electrolyte molecules between a graphite cathode and anode. Abstract : A molecular dynamics (MD) simulation with the optimized potentials for liquid simulations-all atom (OPLS-AA) force field was carried out to investigate the dynamic behaviors of organic electrolyte molecules between a graphite cathode and anode. This study considered the tetraethylammonium cation (NEt4 + ) and tetrafluoroborate anion (BF4 − ) in acetonitrile (ACN) solvent. The predicted NEt4 –BF4 solution density at 1 M from the MD isothermal–isobaric ensemble (NPT) is about 0.861 g cm −3, which is very close to the corresponding experimental value. This indicates that the OPLS-AA force field can accurately describe the interactions between these molecules. The detailed diffusion mechanism and the corresponding viscosity solution for different NEt4 –BF4 mole fractions were explored. The charge density distribution of electrolyte molecules between the graphite cathode and anode from MD simulation was further used to obtain the potential drop by solving the Poisson equation and to obtain system capacitance. This study provides a method to determine the proper molar concentration of electrolyte NEt4 –BF4 in ACN solution which can balance ionic conductivity and capacitance to enhance supercapacitor performance.